STUDIES OF STREPTOCOCCAL CELL WALLS VI. : Effects of Adjuvants on the Production of Type-specific Antibodies to Cell Walls and Isolated M Protein - Hayashi, James A. (1961)
Hayashi, James A. (University of Illinois College of Medicine, Chicago) and Gerald Walsh. Studies of streptococcal cell walls. VI. Effects of adjuvants on the production of type-specific antibodies to cell walls and isolated M protein. J. Bacteriol. 82:736–742. 1961.—Mineral oil adjuvant was shown to assist in type-specific immunization of rabbits, when use was made of isolated cell walls or pH 2-extracted M protein from type 14 group A hemolytic streptococci. The antibodies produced were type specific, and passively protected mice that were challenged with virulent type 14 streptococci. A single injection each week for 4 weeks gave good levels of antibody. Simultaneous immunization with three different types of group A streptococci resulted in production of antibodies against all three types.